1988
DOI: 10.1080/07435808809036336
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Lactogen Receptors in Selected Rabbit Tissues During Pregnancy

Abstract: The ontogeny of lactogen receptors in brain, adipose, liver, kidney, adrenal gland, mammary gland, ovarian and uterine tissues of pregnant rabbits was evaluated in this study using 125I bovine prolactin as tracer. Brain and adipose tissues were found to have very low receptor numbers throughout pregnancy (less than 20 fmol/mg of protein), while liver and kidney had higher but constant levels of receptor through the same period (200 and 100 fmol/mg of protein, respectively). Mammary gland and adrenal gland tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…To our knowledge, the presence of GH or its receptors has never been demonstrated in uterus. However, it is known that human myometrium synthesizes decidual-type prolactin [33,34]; prolactin can regulate a number of uterine functions including endometrial proliferation in animals [35,36], and prolactin receptors that can also bind human GH are present in animal uteri [36][37][38][39]. Therefore, the present findings are suggestive of a possible autocrine role for prolactin in human myometrial growth.…”
Section: Discussionmentioning
confidence: 54%
“…To our knowledge, the presence of GH or its receptors has never been demonstrated in uterus. However, it is known that human myometrium synthesizes decidual-type prolactin [33,34]; prolactin can regulate a number of uterine functions including endometrial proliferation in animals [35,36], and prolactin receptors that can also bind human GH are present in animal uteri [36][37][38][39]. Therefore, the present findings are suggestive of a possible autocrine role for prolactin in human myometrial growth.…”
Section: Discussionmentioning
confidence: 54%
“…Receptors for glucocorticoids and PRL have been unequivocally demonstrated in renal cells (Barash et al, 1986;Grissom and Littleton, 1988;Sharma and Timiras, 1988). The kidney has been pointed out as potential target of these hormones.…”
Section: Discussionmentioning
confidence: 99%
“…The kidney has been pointed out as potential target of these hormones. Receptors for glucocorticoids and PRL have been unequivocally demonstrated in renal cells (Barash et al, 1986;Grissom and Littleton, 1988;Sharma and Timiras, 1988). Interestingly, it has reported that the kidney itself expresses the PRL gene, and the parietal epithelial cells of Bowman's capsule are the major sites of the de novo synthesis of PRL in the mouse kidney (Sakai et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A significant reduction in progesterone levels occurred by Day 35, at which time we also observed a significant reduction in the concentration of uterine PRL binding sites. Uteri of rabbits are also reported to have a higher concentration of unoccupied PRL receptors during pseudopregnancy than estrus [19], and peak concentrations of PRL receptors occur by Day 20 of pregnancy [20]. We hypothesized that the observed changes in PRL binding to ferret uterine membranes occurred in response to a shift in blood levels of progesterone, since plasma concentrations of estrogen and PRL exhibited little or no change throughout pseudopregnancy.…”
Section: -Amentioning
confidence: 99%
“…Many of these events may be crucial in preparing the uterus for blastocyst implantation and successful pregnancy. Specific binding sites for PRL have been demonstrated in uteri of humans [17], rabbits [18][19][20], sheep and cows [21,22], rats [23,24], pigs [25], and mink [26].…”
Section: Introductionmentioning
confidence: 99%